2020
DOI: 10.1038/s41598-020-69446-5
|View full text |Cite
|
Sign up to set email alerts
|

A model for classification of invasive fungal rhinosinusitis by computed tomography

Abstract: Our purpose was to classify acute invasive fungal rhinosinusitis (AIFR) caused by Mucor versus Aspergillus species by evaluating computed tomography radiological findings. Two blinded readers retrospectively graded radiological abnormalities of the craniofacial region observed on craniofacial CT examinations obtained during initial evaluation of 38 patients with eventually pathology-proven AIFR (13:25, Mucor:Aspergillus). Binomial logistic regression was used to analyze correlation between variables and type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In a recent study, it was found that AIFR caused by Aspergillus had predominantly unilateral findings whereas disease due to Mucor species, the species most often associated with CAM, had greater bilateral sinonasal involvement. 4 …”
Section: Imaging Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was found that AIFR caused by Aspergillus had predominantly unilateral findings whereas disease due to Mucor species, the species most often associated with CAM, had greater bilateral sinonasal involvement. 4 …”
Section: Imaging Featuresmentioning
confidence: 99%
“… 3 The recent COVID 19 pandemic has witnessed a high surge in cases of AIFR especially of the Mucor species, which was the less common cause of AIFR in the pre covid era, second to Aspergillus. 4 The Indian subcontinent witnessed a dramatic spurt in cases of COVID associated mucormycosis (CAM) and by June 7, 2021, a spate of 28,252 cases of mucormycosis were reported, 86% having a history of COVID-19 infection. 5 , 6…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus has a tendency towards unilateral involvement (Fig. 12 ) compared to Mucor [ 13 ]. Mucor , however, has a marked tendency to cause invasive thrombosis of vessel walls and the characteristic “black turbinate sign” (non-enhancement of nasal mucosa or turbinates on CECT/CEMRI) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillosis more commonly has sinocranial involvement in the absence of orbital involvement, dural-based T2 hypointense masses on MRI, and unilateral (versus bilateral in mucormycosis) sinonasal cavity involvement. 7 On the other hand, thrombosis due to the involvement of vessel walls and a black turbinate sign are more common in mucormycosis infection. 4 Recent case series have been published describing the imaging findings of COVID-19-associated rhino-oculo-cerebral mucormycosis.…”
Section: Covid-19-associated Rhino-ocular/ Rhino-oculo-cerebral Mucor...mentioning
confidence: 99%